The Effect of Quality of Service on Customer Satisfaction on PT. PLN (Persero) Rayon Soppeng Regency - Nur Magfirah Mukti; Haedar Akib; Sirajuddin Saleh; Risma Niswaty; Aris Baharuddin (Universitas Negeri Makassar, 2022)
This research aims 1) to find out the effect of service quality on customer satisfaction on PT. PLN (Persero) Rayon Soppeng Soppeng District 2) to know customer satisfaction at PT. PLN (Persero) Rayon Soppeng Soppeng District 3) to know the effect of service quality on customer library at PT. PLN (Persero) Rayon Soppeng Soppeng Regency. This study uses a quantitative approach with descriptive research types. Data collection techniques are conducted through observations, questionnaires/ questionnaires, interviews and documentation. The number of samples in this study was 99 people, and using quota sampling techniques. The methods of analysis used are descriptive statistical analysis and inferential analysis. The results showed that the indicators used on each variable then the results showed where the quality of service PLN (Persero) Rayon Soppeng Soppeng Soppeng district is in the category of very good with the achievement of 90.00 percent. And for the satisfaction of participants PLN (Persero) Rayon Soppeng Soppeng district is in the high category with the achievement of 90.00 percent. While based on the correlation test obtained an R value of 0.887 means that there is a very strong / high correlation between the two variables. Based on the results of data analysis so that it can be concluded that the quality of service at PT. PLN (Persero) Rayon Soppeng Soppeng District is very good because the percentage of service quality has high values or a high percentage. Customer Satisfaction at PT. PLN (Persero) in Rayon Soppeng Soppeng District is very good because the percentage of customer satisfaction has high values or a high percentage. There is a significant influence between the quality of service to customer satisfaction at PT. PLN (Persero) Rayon Soppeng Soppeng Regency.